Mastering Excel : a problem-solving approach - Gips, James, 1946- (New York : John Wiley and Sons, 1997)
Creating simple worksheets. Changing the appearance of the worksheet. Simple functions and the fill operation. Operations on cells. Relative vs. absolute addressing...
Keywords: Computer programs; Microsoft Excel for Windows; Microsoft Excel for Windows; Business -- Computer programs; Electronic spreadsheets